(3fXe GdOQQ aj JfGSH GdBjGJ hGdShQs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s ((3YHOGdbGOQ eMeO Hf YHOGddg Hf CMeO GdZQjGfj s)
(3ChdgG (B:s
(3ShQI U s
(3BNQgG (B:s
(3BNQ ShQI GdbJGd s
(3GdfSNI HgG MhGTs
(3gfGc Tc aj Cf GdfGSN gh cGJH GdeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B49 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1961s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs